Anti-counterfeiting applications by photochromism induced modulation of reversible upconversion luminescence in TiO2:Yb3+, Er3+ ceramic. Issue 16 (7th April 2022) - Haider, Asif Ali; Cun, Yangke; Bai, Xue; Xu, Zan; Zi, Yingzhu; Qiu, Jianbei; Song, Zhiguo; Huang, Anjun; Yang, Zhengwen
Abstract : Reversible photochromism and reversible UCL modulation of TiO2 :Yb 3+, Er 3+ ceramics were reported when alternating 405 nm LED and 808 nm laser irradiation. The photochromic TiO2 :Yb 3+, Er 3+ ceramics are promising materials in the field of anti-counterfeiting. Abstract : Photochromism-induced reversible upconversion luminescence modulation has received extension attention due to its promising applications in anti-counterfeiting, optical storage, and switches. In this work, photochromic TiO2 :Yb 3+, Er 3+ ceramics were prepared by a high temperature solid state method. The white TiO2 :Yb 3+, Er 3+ ceramics turn to pink-gray color under 405 nm LED illumination for 27 min, and the color of the photochromic sample was restored to the primitive state after 808 nm laser irradiation for 170 s. The photochromic mechanism of TiO2 :Yb 3+, Er 3+ ceramics is related to the formation of Ti 3+ defects and oxygen vacancy caused by Yb 3+ and Er 3+ codoping. The cycle measurements between alternate irradiation of 405 nm and 808 nm light stimulation show the good reversibility between photochromic and bleaching processes. Under 980 nm excitation, the upconversion luminescence properties of photochromic TiO2 :Yb 3+, Er 3+ ceramics were investigated, exhibiting excellent reproducibility for the photochromism-induced upconversion luminescence modification. The application of TiO2 :Yb 3+, Er 3+ ceramics as an anti-counterfeiting agent was designed, and the results reveal the potential application of TiO2 :Yb 3+, Er 3+ ceramics in the anti-counterfeiting field.